Satisfaction Derived by the Users' of Petrocard in Coimbatore City - Vijaykumar, R.; Vijaykumar, P. (Indian Journal of Marketing, 2005)
Bharat Petroleum Corporation Limited (BPCL) is the second largest oil company, in terms of market share and processing of the crude oil, in India. It processes about nine million metric tonnes of crude oil per annum. The company has its network throughout India and it reaches seven hundred million Indians in some way in their every day life. The company launched a programme known as "Smart Fleet" to satisfy the fuel requirements of fleet owners and corporates and this programme received an enthusiastic response from over 2500 clients in a very short span of time. With a view to satisfy the similar type of requirements of the individuals, who consume fuel for operating their vehicles, the company has launched a programme known as "Petro Card" during March 2000 in Mumbai as an experiment. As the programme received an excellent response from the individuals, the company has extended the same to the customers all over India.